Effects of warranty on purchase decision of electronic products: an empirical research from the perspective of Bangladesh - Ullah, G. M. Shafayet; Islam, Md. Rifayat (© 2011 Industrial Engineering Letters, 2016)
This article was published in Industrial Engineering Letters [© 2011 Industrial Engineering Letters] and the definite version is available at : http://iiste.org/Journals/index.php/IEL/article/view/637/530 The article website is at: http://iiste.org/Journals/index.php/IEL/index